2014
DOI: 10.5853/jos.2014.16.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Acute Ischemic Stroke Treatment

Abstract: Although intravenous administration of tissue plasminogen activator is the only proven treatment after acute ischemic stroke, there is always a concern of hemorrhagic risk after thrombolysis. Therefore, selection of patients with potential benefits in overcoming potential harms of thrombolysis is of great importance. Despite the practical issues in using magnetic resonance imaging (MRI) for acute stroke treatment, multimodal MRI can provide useful information for accurate diagnosis of stroke, evaluation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 98 publications
2
110
0
8
Order By: Relevance
“…Although our data cannot provide evidence of this hypothesis by comparing CIS with perfusion weighted imaging (PWI) or volume of infarction on diffusion weighted imaging (DWI),7 8 several arguments are consistent with this hypothesis. Firstly, the lack of enhancement of the brain at the capillary phase—which defines a poor CIS—is due to either a severe decrease in cerebral blood volume and/or a significant increase in mean transit time.…”
Section: Discussionmentioning
confidence: 63%
“…Although our data cannot provide evidence of this hypothesis by comparing CIS with perfusion weighted imaging (PWI) or volume of infarction on diffusion weighted imaging (DWI),7 8 several arguments are consistent with this hypothesis. Firstly, the lack of enhancement of the brain at the capillary phase—which defines a poor CIS—is due to either a severe decrease in cerebral blood volume and/or a significant increase in mean transit time.…”
Section: Discussionmentioning
confidence: 63%
“…In the previous studies, 9% [11] and 21% [12] of the patients with LMI were reported to accompany cerebellar infarcts, and MRI was used in 67 and 100% of these patients respectively. The relatively high proportion of LMI-plus in our series may be attributed to (1) the inclusion of patients with extra-cerebellar lesions and (2) our use of DWI that can reliably locate acute small infarcts in the posterior circulation territory [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Similar to the cases of logotherapy in patients with speech disorders or early kinesitherapy in patients with motor dysfunction, visual impairments require complex management [9][10][11][12]. It is essential that patients with visual disorders are thoroughly examined by a neurologist and ophthalmologist and undergo follow-up neuroimaging visualising and assessing the extent of cerebral stroke (preferably using MRI) as well as perimetry tests [13][14][15]. Complex medical attention, objectivisation of disorders, and evaluation of prognosis favourably affect the patient`s mental condition, which prevents reactive mood disorders enhancing disability [16].…”
Section: Discussionmentioning
confidence: 99%